Ointment Formulation from Collagen Extract of Tilapia Fish Skin (Oreochromis niloticus) for Healing Burns in Mus musculus - Nugroho, Romy Triadi; Saputra, Gilang; Aini, Annisa Nurul; Dewi, Aisha Andini Indira; Tarigan, Indra Lasmana (Pharmaceutical Journal of Indonesia, 2022)
Introduction: Burns are injuries that caused by contact with a heat source. The natural alternative burn treatment can use hydrolyzed collagen derived from aquatic ecosystems, one of them is fish.Objectives: The aim of this research was to find the optimum formulation of tilapia fish collagen extract ointment.Methods: Fish skin that has been separated was prepared using the solution of NaOH 0,1 N and Butyl Alcohol 10%.Then the fish skin was extracted using a 0.5 M acetic acid solution and precipitated with a 0.9 M NaCl solution. Then, dialysis was performed using a plastic membrane (14 KDa) in a 0.1 M acetic acid solution and distilled water to obtain a wet collagen extract which was then in the FreezeDryer to reduce the water content.Results: The collagen extract obtained was used for ointment formulations with different concentrations of collagen extract, that is 5%, 10%, and 15% and 2 additional miana plant extracts were used with collagen extract 5+5% and 10+10%. The results of the formulation were tested on burns with a diameter of 0.715 cm in mice.Conclusion: From the results of the effectiveness test, the formulation with 15% collagen extract showed effective results. Indicated by the rate of wound healing in mice observations